Are acute:chronic workload ratios of perceived exertion and running based variables sensible to detect variations between player positions over the season? A soccer team study - Nobari, Hadi (2022)
Background: The aim of this study was to describe and compare the in-season variations of acute: chronic workload ratio (ACWR) coupled, uncoupled, and exponentially weighted moving average (EWMA) through session rating of perceived exertion (s-RPE), total distance (TD), high-speed running distance (HSRD) and sprint distance (SPRINT) in three diferent periods of an elite soccer season according to player positions. Methods: Twenty male elite players (age: 29.4±4.4) from an Asian First League team were daily monitored for twenty consecutive weeks during the 2017–2018 in-season. Forty-seven trainings and twenty matches were moni tored using global positioning system units (GPS) to collect TD, HSRD and SPRINT. Through the collection of s-RPE, TD, HSRD, and SPRINT by ACWR and EWMA were calculated for each training session. Results: The results revealed that according to diferent periods of the season, workload measures observed in mid season were meaningfully higher compared with early-season (g=ranging from 0.53 to 4.98) except for EWMASPRINT. In general, wingers and strikers tended to have greater scores in workload measures compared to the defenders and midfelders (g=ranging from 0.41 to 5.42). Conclusions: These fndings may provide detailed information for coaches and sports scientists regarding the vari ations of acute and chronic workload ratio and external loading in-season and between player positions in an elite soccer team